h-Refined Schwarz-Krylov Solution for Hydrodinamics and Mass Transport in a PC Cluster - Dorneles, Ricardo Vargas; Rizzi, Rogerio Luis; Diverio, Tiarajú A.; Navaux, Philippe O. A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This work presents a parallel solution, implemented in a PC cluster, using MPI library, to the simulation of hydrodynamics and mass transport in the Rio Guaiba. The governing equations of hydrodynamics and scalar transport of substances are defined in space-staggered grids, where the finer grid is nested in the coarser grid and built through interpolation. The PDEs are discretized using finite differences using upwind and centered difference techniques to generate a semi-implicit numerical scheme. To build the local subproblems a version of bissection algorithm was used to partitionate the numerical grid, and Schwartz additive method was used to build the overlapping Local solutions are obtained using Krylov subspace iterative methods.